Green Marketing Perspective: Eco-Consciousness dan Sustainable Packaging sebagai Determinan Green Purchase Behavior dengan Mediasi Consumer Attitudes - Hasnidar; Achmad Ridha (www.amertainstitute.com, 2025)
This study analyzes the influence of Eco-Consciousness and Sustainable Packaging on Green Purchase Behavior with Consumer Attitude as a mediating variable among coffeeshop consumers in Makassar. Using a quantitative causal approach, data were collected from 150 respondents and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Eco-Consciousness and Sustainable Packaging positively and significantly influence Consumer Attitude. Furthermore, Consumer Attitude has a strong and significant effect on Green Purchase Behavior. Both Eco-Consciousness and Sustainable Packaging also have direct positive effects on Green Purchase Behavior, indicating that consumers engage in environmentally responsible purchasing behavior not only because of their attitudes but also due to their awareness of environmental issues and perceptions of sustainable packaging. Mediation analysis confirms that Consumer Attitude significantly mediates the relationship between Eco-Consciousness and Green Purchase Behavior as well as between Sustainable Packaging and Green Purchase Behavior. These findings highlight the importance of integrating ecological values and sustainable packaging efforts into green marketing strategies, particularly in the coffeeshop industry. Overall, the study contributes to the green marketing literature by presenting an integrated model that explains how psychological factors and sustainable product attributes shape environmentally friendly purchasing behavior.